Numerical characterisation of hollow sphere composites based on perporated inclusions [electronic resource] - Mohd. Ayub Sulong, 1986- (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012